Hemidesmus indicus COMMONLY KNOWN AS INDIAN SARASAPARILLA- AN UPDATE - LAKSHMI .T; RAJENDRAN .R (International Journal of Pharma and Bio Sciences, 2013)
Hemidesmus indicus is widely used in Ayurveda for treatment of various disease conditions. It is used as a tonic, demulcent, diaphoretic, diuretic and blood purifier. The therapeutic action of the herb is due to presence of major chemical constituents like coumarinolignoids hemidesmine and hemidesmin. This herb is beneficial in skin disorders ,urinary tract infections and to treat kidney failure. Based on the scientific research the article is reviewed to reveal the therapeutic aspects of the herbal extract for the beneficial of further research.